2015
DOI: 10.15406/frcij.2015.01.00008
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Sex from the Upper Limb in Modern Cretans with the Aid of ROC-Analysis: A Technical Report

Abstract: Discriminant function analysis is one of the most popular methods employed for grouping specimens according to optimal combination of linear measurements. Many studies have used this method with the objective of producing population specific formulae for sex estimation from different skeletal parts of the skeleton. This study focuses on the long bones of the upper limb using Receiving operation characteristics (ROC) curves. A total of 173 well preserved skeletons of Cretan origin were used. A total of 12 measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
7
0
3
Order By: Relevance
“…To date there are no data available on modern Greek-Cypriots while a large number of studies have been emerging recently for neighbouring Cretans [9,21,[31][32][33][34][35] and mainland Greeks [36][37]. The same situation holds true for Turkish-Cypriots with an increasing number of studies from mainland Turkey appearing recently [26,[38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date there are no data available on modern Greek-Cypriots while a large number of studies have been emerging recently for neighbouring Cretans [9,21,[31][32][33][34][35] and mainland Greeks [36][37]. The same situation holds true for Turkish-Cypriots with an increasing number of studies from mainland Turkey appearing recently [26,[38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The recommendations for good practise in forensic anthropology by the American Board of Forensic Anthropology [45], the British Association for Forensic Anthropology [COP BAHID, 2015] [46] and the Forensic Anthropology Society Europe [FASE Basic Workshop, Coimbra, 2016] [47] mandate the application of population specific standards for any method of biological profiling; thus this work constitutes a step in the development of osteometric standards for Cyprus. Biometric datafor Cretans have been published before for cranial and postcranial elements[9,21,[31][32][33][34][35]…”
mentioning
confidence: 99%
“…Nevertheless, standard approaches do not always meet the needs of certain crime or death scenes, especially when highly decomposed or skeletonized bodies are involved [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Dimensions from the upper long bones (humerus, radius, ulna, and clavicle) have been used to successfully distinguish between the sexes in several European (Cowal and Pastor 2008;Bašić et al 2013;Kranioti and Tzanakis 2015), Asian (Sakaue 2004;Lee et al 2014) and African populations (Steyn and Işcan 1999;Barrier and Abbé 2008). In mentioned studies, different measurements have been shown to be good indicators of sex dimorphism.…”
Section: Introductionmentioning
confidence: 99%